The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.2175/106143017x15023776270629
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pollution on Freshwater Organisms

Abstract: This review covers research papers and scientific literature published in the year 2016 on the effects of anthropogenic pollutants on freshwater organisms. In the first, the review begins with two broad sections thate are mainly focused on research reviews and broad field studies and surveys. This is followed by reviews of research categorized in sections to reflect the pollutant class. These sections include wastewater, stormwater and non-point source pollution, nutrients, sediment cap materials and suspended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Farmers specifically referred to seawater intrusion as a result of overpumping (37%), irrigation with saline water (12.6%), excessive application of fertilizer (10.9%), irregular irrigation patterns (9.2%) and mismanagement by labourers (5%) (Figure 5c). These findings are consistent with the studies of Choudri, Baawain, and Ahmed (2015), Choudri, Baawain, Ahmed, Al‐Sidairi, and Al‐Nadabi (2015) and Choudri et al (2018). Moreover, more than half of the respondents indicated that they do not receive any assistance or recommendations on how to alleviate soil salinity (Figure 5d).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Farmers specifically referred to seawater intrusion as a result of overpumping (37%), irrigation with saline water (12.6%), excessive application of fertilizer (10.9%), irregular irrigation patterns (9.2%) and mismanagement by labourers (5%) (Figure 5c). These findings are consistent with the studies of Choudri, Baawain, and Ahmed (2015), Choudri, Baawain, Ahmed, Al‐Sidairi, and Al‐Nadabi (2015) and Choudri et al (2018). Moreover, more than half of the respondents indicated that they do not receive any assistance or recommendations on how to alleviate soil salinity (Figure 5d).…”
Section: Resultssupporting
confidence: 92%
“…Additionally, the detrimental effects of intensive and unsustainable agricultural practices, coupled with the use of low‐quality saline water for irrigation, contribute to the problem. Furthermore, the overpumping of groundwater in coastal areas like Al‐Batinah and Salalah leads to seawater intrusion, exacerbating soil salinity levels in Oman (Abdalla et al, 2010; Al‐Ajmi et al, 2002; Askri & Ali Al‐Shanfari, 2017; Choudri, Baawain, & Ahmed, 2015; Choudri, Baawain, Ahmed, Al‐Sidairi, & Al‐Nadabi, 2015; Shammas & Jacks, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that the bioaccumulation of organic compounds in an aquatic environment is more related to partitioning coefficients than their absolute exposure concentrations. Furthermore, the fate of the environmental contaminants is not only affected mainly by their physio-chemical characteristics, but also biological processes including environmental parameters that play a critical role in the uptake of these chemicals [44][45][46][47]. Biological factors including individual size, life cycle, feeding type, lipid content, respiration strategy, habitat and metabolic processes may affect the uptake and sensitivity of individuals to the contaminants [48][49][50]; however, the available information is still limited [51].…”
Section: Resultsmentioning
confidence: 99%
“…Different studies reported their effects on physiology, which can lead to the development of chronic degenerative diseases with epidemiological impact [1][2][3]. The residues of these compounds have been reported in food, water, sea life, birds, and biological substrates such as different tissues and breast milk [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%